Investigation of Burnout Levels of Physical Education and Sports Teachers during Covid-19 Period - Berna Karakoç,; Önder Karakoç,; Özgür Aktaş,; Murat Arslan, (Journal of Educational Issues, 2024)
Due to the COVID-19 pandemic, it was decided to conduct educational activities online and the burnout status of teachers who suddenly switched to distance education became a matter of curiosity. This study was carried out to examine the burnout levels of physical education and sports teachers during the Covid-19 period and to examine possible changes that may occur after this process by getting information about how they will approach their profession. profession and students. In this context, the research group consists of 210 physical education and sports teachers, 142 men and 68 women. These teachers took a break from face-to-face education due to the pandemic and continued their lessons with online education. The Maslach Burnout Inventory and 3 semi-structured questions were used to find out the emotional states of physical education and sports teachers and how they approached students during and after the pandemic. IBM SPSS 22 statistical program was used in the analysis of the data obtained from the scale. Analysis of normality showed that the data were normally distributed. Parametric test independent samples t-test was used to compare paired groups, one-way ANOVA was used to compare more than two groups and the level of significance was accepted as (p)<.05. In addition, the content analysis method was used in the analysis of the data obtained from the semi-structured interview form. The results showed that physical education and sports teachers participating in the study experienced moderate burnout. It was determined that the most negatively affected aspect of teachers was emotional exhaustion during the Covid-19 pandemic. There was no significant difference between the burnout levels of physical education and sports teachers according to the variables of gender, age, professional seniority, the type of sports they do. Physical education and sports teachers stated that they missed their students and they wanted face-to-face education to start at school, while more than half of the teachers stated that their attitudes to students will change after the pandemic.